Comparison between Exposure of Ciprofloxacin and Cefotaxime on Developing of Escherichia coli ESBL - Amin, Muhammad; Wasito, Eddy Bagus; Triyono, Erwin Astha (Folia Medica Indonesiana, 2020)
This study aimed to compare ciprofloxacin and cefotaxime exposure to develop ESBL producing Escherichia coli (E. coli). A total of 16 isolates of cefotaxime sensitive E. coli and ciprofloxacin were exposed to ciprofloxacin and cefotaxime for 14 days using the Kirby-Bauer antibiotic disc diffusion method. Colonies that grew on the edge of the inhibiting zone were exposed each day by the same method. Furthermore, we observed the occurrence of resistance to cefotaxime as ESBL screening test. Isolates were resistant, the following day the ESBL was confirmed by the Modified Double Disk Sinergy Test (MDDST) method using Cefotaxime (CTX), Ceftazidime (CAZ), Aztreonam (ATM), and Amoxilin Clavulanate (AMC) antibiotic discs. From 16 isolates of ESBL producing E. coli exposed to ciprofloxacin, it was obtained 4 (25%) to ESBL E. coli. ESBL production occurred after E. coli was exposed to ciprofloxacin on days 5, 6, 7, and 12. While those exposed to cefotaxime none becomes ESBL E. coli. There was no difference between ciprofloxacin and cefotaxime exposure to develop ESBL producing E. coli (p=0.101; Chi-square).